Olssons trädgård : ett examensarbete som handlar om att lyssna när en plats berättar - Lindgren, Lisa (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
This master thesis is about a place that has a story to tell. Olsson's garden came about when Mr Carl Oscar Olsson acquired a piece of land in Landalabergen in the beginning of the 1930's and at that time he started his industrious work of uniting much of Sweden's flora in his garden. Since the very beginning Olsson's garden has played a lot of different rolls in a variety of situations and meant different things for different people.